Behavior Model of the Producer who Believes in Life After Death: A Mathematical and Geometric Approach - Ezzati, Morteza (International Journal of Islamic Economics and Governance, 2024)
Producer behavior is one of the important theoretical challenges in the field of religion effect on the economy. In this field, theories have been presented. But these theories also have shortcomings. Belief in the afterlife effects on producer’s behavior, this article attempts to analyze and to explain the effect of belief in life after death and satisfaction in that life on the producer’s behavior by recalling the producer’s motivation and goal and giving it a framework compatible with religion. This article is in the framework of theorizing and its analysis method is the method of logic along with mathematical and geometrical analysis. Among the findings of this study is the explanation of the effect of religious beliefs on producer behavior, how to determine the balance, the optimal size of production on the producer’s productive behavior with mathematical and geometrical methods. The main innovation of this paper is to present a theory on the behavior of the faithful producer. In addition, a special innovation of this paper is to present mathematical and geometric analyses in explaining the behavior of the faithful producer.